Negotiating Futures: How Schools Shape Belonging for Young Newcomers in Belgium, Denmark, Norway, and Sweden. - Spaas, Caroline; Osman, Fatumo; Skovdal, Morten; Hilden, Per Kristian; Derluyn, Ilse; Durbeej, Natalie; Sarkadi, Anna; Primdahl, Nina L.; Andersen, Arnfinn J.; Verelst, An; Colpin, Hilde; De Haene, Lucia (Journal of Child & Family Studies, 2024)
Scholars draw increasing attention to the importance of belonging for young refugees' and migrants' well-being, indicating the need to develop an in-depth understanding of their experiences seeking to belong in resettlement. For refugee and migrant newcomers, schools might constitute particularly significant spaces in their negotiation of belonging, due to being a central developmental and acculturative context in resettlement, and a context where newcomers are situated within interpersonal and cultural positions of their families, home, and host society. Rooted in a conceptualization of belonging as a dynamic, plural, and relationally negotiated experience, this study explores how young newcomers' negotiation of belonging takes shape within the school context and how their experiences seeking to belong relate to their well-being. To that, the study engages with the qualitative inquiry of 163 newcomers' (age 11–24) experiences through focus groups conducted in Belgium, Denmark, Norway, and Sweden. Cross-national, joint thematic analysis resulted in two themes: 1. Ambivalences shaping belonging; and 2. Challenging barriers to belonging. Our findings suggest that, in school, newcomers meet opportunities and barriers in their negotiation of belonging that takes shape at the intersection of family, transnational, and host society relations. Schools furthermore seem central spaces for newcomers to exercise agency and creativity in their search for belonging in resettlement. Our findings spark thought on belonging as a reconstructive process in coping with migration and have implications for how schools can support belonging and well-being, through engaging with life stories of migration and the plurality of meanings encroaching upon newcomers' school trajectories. Highlights: Our study highlights underexposed voices of a large, multi-national sample of newcomer youth, revealing rich thematic insights. It highlights the significance of family, transnational, and host society relations in newcomers' negotiation of belonging. Our findings point to the multilayered meaning of belonging in coping with migration. The study uncovers important dynamics of agency and creativity in newcomers' search for belonging in the school context. Our findings evoke reflection on belonging as a reconstructive process supporting coping and well-being after migration.